(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Six honey samples were collected from various locations in Anambra and Enugu states in southeastern Nigeria and analyzed for physicochemical characteristics and mineral composition. pH, moisture, protein, fats, ash, polyphenol, free acidity, hydroxymethylfurfural (HMF), and sugar were among the physicochemical parameters studied. Minerals such as potassium, calcium, zinc, magnesium, sodium, cadmium, and lead were also investigated. The samples had pH values ranging from 4.00 - 4.40. Moisture content ranged from 8.95% - 14.30%, ash 0.21 - 0.54%, protein 0.21- 0.74%, fat 0.00 - 0.50%, polyphenol 2.75 - 12.00%; free acidity 33.60 - 89.890 meq kg-1 and HMF 18.70 - 75.43 mg/kg. The sugar assays revealed that all of the honey samples contained the appropriate quantity of sugar for acceptable quality honey, albeit there were substantial variances in the values recorded across the locations. The mineral composition revealed that potassium was the most abundant element, followed by zinc, calcium, magnesium, and sodium. In the samples, no cadmium or lead was found. The results of the evaluated honey samples revealed that the majority of the measured parameters recorded met international standards, indicating that they were safe for human consumption.